Insights into the late Cenozoic structural deformation and tectonic stress field of the Qiabuqia region, Gonghe Basin, northeastern Qinghai–Tibetan Plateau - Yang, Zhang; Qingda, Feng; Fucheng, Li; Linyou, Zhang; Chao, Zhang; Senqi, Zhang; Dunpeng, Li; Zhen, Yan; Jian, Song; Lei, Fu; Zhaoxuan, Niu (Frontiers in Earth Science, 2023)
In addition to overall uplift of the Qiabuqia region during the Late Cenozoic, three deformation stages can be identified in the northeastern Qinghai–Tibet Plateau. Specifically, these deformation stages were recognized in areas east of the Gonghe Basin that surrounds Waliguan Mountain and include: 1) Late Miocene to Late Pliocene deformation—dominated by thrust napping with dextral strike-slipping; 2) Early Pleistocene to late middle period of Pleistocene deformation—fault structures were dominated by the dextral strike-slipping with thrust napping; and 3) end of Late Pleistocene to Middle Holocene deformation—thrust napping slowed down and finally braked, while the shallow surface began to loosen and extend at Qiabuqia region’s rear-edge. DR4 borehole drilling data indicate that the Xiangshuihe Formation’s buried depth is ∼1,000 m. The Xianshuihe Formation’s top section is characterized by normal fault–type (NF) tectonic stress, while the maximum principal tectonic stress (σ1) is perpendicular and the minimum principal tectonic stress (σ3) is horizontal. In contrast, the deep basement is characterized by thrust fault (TF) and strike-slip (SS) tectonic stress, while the σ1 is in the NE-SW direction, ranging from 20.1° to 75.3° with an average of 40.0°. Based on the aforementioned observations, it can be inferred that there are three sets of hidden faults in the basement of the Qiabuqia region: 1) the NW–NNW trending compressional–torsional faults; 2) the NE trending tensional–torsional faults; and 3) the NWW trending compressional–torsional faults. The findings in this study can potentially offer a robust geological basis for exploring and utilizing hot, dry rock resources within the Gonghe Basin.